Genome-wide scans - Province, Michael (Henry Stewart Talks, 2004)
Genome-wide vs. candidate gene search methods, Linkage vs. association, How to cope with multiple comparisons, Ordered sequential methods, Latest meta-analysis methods for LOD score analysis
Archived at 2021/02/25